Development Of A Portable Low Strain Rate Testing Machine - Munusamy, Sharven (Universiti Sains Malaysia, 2022)
Slow strain rate testing, is important in understanding the mechanical behaviour of material. It entails applying a slow dynamic strain with a constant extension rate to a specimen. Typical Universal Tensile Machine (UTM) can be used to determine the strain rate of a material. However, a machine that can couple low and high strain rate testing at a reasonable cost is usually not easily accessible. Therefore, this paper attempts to propose a design of concept that can be used in a high strain rate testing machine as well as to independently conduct low strain rate testing. Critical components such as the spring nut holder, pulling rod, moving grip holder and stationary grip holder were designed and fabricated. Whereas the frame which holds these components in place was reused from the machine part. A testing was done to verify that the prototype can perform as it is intended by comparing results with a UTM Gunt machine. The extension curve of the both machine and prototype were similar and the prototype was rigid (did not endure significant bending during the test). Finally, a scheme to connect to a SHPB machine to allow high strain and low strain testing capability on a unique SHPB setup was proposed.